2020
DOI: 10.1111/bph.15225
|View full text |Cite
|
Sign up to set email alerts
|

The low‐expression programming of 11β‐HSD2 mediates osteoporosis susceptibility induced by prenatal caffeine exposure in male offspring rats

Abstract: Background and Purpose Prenatal caffeine exposure (PCE) can cause developmental toxicity of long bones in offspring, but the long‐term effects and the underlying mechanism have not been fully clarified. Here, we investigated the effects of PCE peak bone mass accumulation and osteoporosis susceptibility in offspring and its intrauterine programming mechanism. Experimental Approach Pregnant Wistar rats were administrated intragastrically with saline or caffeine (120 mg·kg−1·day−1) on gestational days 9–20. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Therefore, it is necessary to evaluate the expression stability of housekeeping genes in a specific model and select appropriate ones according to the actual situation. At present, the studies on fetal‐originated diseases are increasing (Liu et al, 2020; Xiao et al, 2020; Zhang et al, 2020), but the expression stability of housekeeping gene under the relevant models has not been comprehensively and systematically studied. DuBois et al found that the maternal low‐protein diet changed the expression levels of housekeeping genes in an age, sex, and organ‐dependent manner in rat offspring (DuBois et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to evaluate the expression stability of housekeeping genes in a specific model and select appropriate ones according to the actual situation. At present, the studies on fetal‐originated diseases are increasing (Liu et al, 2020; Xiao et al, 2020; Zhang et al, 2020), but the expression stability of housekeeping gene under the relevant models has not been comprehensively and systematically studied. DuBois et al found that the maternal low‐protein diet changed the expression levels of housekeeping genes in an age, sex, and organ‐dependent manner in rat offspring (DuBois et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…30 At 30 mg/kg•d, the changes of multiple indicators were significant, and there was a significant dose-dependent relationship with different doses of 30, 60, and 120 mg/kg•d. [30][31][32] Therefore, to fully reflect the developmental toxicity of caffeine and obtain a stable IUGR model, we used a maximum concentration of 120 mg/kg•d caffeine in this study. Thus, caffeine concentrations of 30, 60, and 120 mg/kg•d were selected for the animal experiment in this study.…”
Section: Rationality and Significance Of Caffeine Doses And Fetal Rats Gender Used In This Studymentioning
confidence: 87%
“…( Figure 1 ) In addition, a recent study shows that HDAC11 contributes to osteoporosis susceptibility and reduced peak bone mass through a mechanism of 11β-HSD2’s low-functional programming. This is triggered by corticosterone through GR/HDAC11 signaling, which amplifies the effect of corticosterone on inhibiting the function of BMSCs in osteogenesis ( 141 , 142 ). However, studies on diabetic osteoporosis, lipoid nephrosis, fatty liver disease and obesity cardiomyopathy are still lacking.…”
Section: Discussionmentioning
confidence: 99%